2017
DOI: 10.1016/j.annemergmed.2017.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decisionmaking in the Emergency Department: A Guiding Framework for Clinicians

Abstract: Shared decisionmaking (SDM) has been proposed as a method to promote active engagement of patients in emergency care decisions. Despite the recent attention SDM has received in the emergency medicine community, including being the topic of the 2016 Academic Emergency Medicine Consensus Conference, misconceptions remain regarding the precise meaning of the term, the process, and the conditions under which it is most likely to be valuable. With the help of a patient representative and an interaction designer, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 32 publications
1
58
0
1
Order By: Relevance
“…Although research has suggested that younger and more educated patients are more likely to want SDM as opposed to physician‐directed decision making, we intentionally decided against analyzing subsets to avoid promoting the perception that we as physicians can tell by demographics and clinical interactions how much involvement a particular patient would like. Our data suggest that if clinical equipoise exists, nearly all ED patients would like to be aware of the options available to them …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Although research has suggested that younger and more educated patients are more likely to want SDM as opposed to physician‐directed decision making, we intentionally decided against analyzing subsets to avoid promoting the perception that we as physicians can tell by demographics and clinical interactions how much involvement a particular patient would like. Our data suggest that if clinical equipoise exists, nearly all ED patients would like to be aware of the options available to them …”
Section: Discussionmentioning
confidence: 89%
“…This “healthier‐person” bias may have been introduced because only stable and alert patients were approached and sicker patients may have been more likely to refuse. While being alert is a prerequisite for SDM, hemodynamically stability is not, if clinical equipoise exists and time allows . Furthermore, as this survey was clearly about SDM, it is possible that the same forces that encourage people to defer to physicians may also encourage them to agree with survey questions—our knowledge of the pitfalls of surveys suggest that an “acquiescence effect” may account for 10% of agreement with positive statements …”
Section: Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…1 A recently published framework suggests that only 3 factors are necessary for SDM to be appropriate in the ED: some degree of clinical equipoise, a willing and able patient or proxy, and time. 2 Although research in the field of SDM has been ongoing for several decades, recent attention to the opportunities for SDM in the Emergency Department (ED) has heightened the need for ED-specific research. 3,4 Several studies have examined SDM from the perspective of the ED physician, recognizing the importance of the physician-as-stakeholder.…”
Section: Introductionmentioning
confidence: 99%
“…Probst et al have proposed a framework for shared decision-making in the ED, which they argue is applicable in cases where 1) there is more than one reasonable medical option, 2) the patient is willing and able to make decisions, and 3) there is sufficient time. 15 This framework can be applied to cases of renal colic. As we have discussed, there is growing evidence for avoiding CT scans in patients with suspected kidney stones by using different imaging pathways.…”
Section: Discussionmentioning
confidence: 99%